2013
DOI: 10.17221/6905-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed, postnatal development, and nutrition on mRNA expression of the FTO gene in porcine muscle and its relationship with intramuscular fat deposition

Abstract: ABSTRACT:The effects of breed, development, and nutrition on mRNA expression of the fat mass and obesityassociated gene (FTO) and its relationship with intramuscular fat (IMF) content in porcine muscle (m. longissimus dorsi; m.l.d.) were estimated. Purebred Jinhua, Zhongbai, Yorkshire, Duroc, Duroc × Zhongbai (DZ), and Duroc × Yorkshire × Landrace (DYL) pigs were used to investigate the effect of breed. Pigs weighing 2.5, 10, 20, 40, 60, and 100 kg were selected to study the effects of different stages of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Tao et al (2013) also presented the data that the IMF content was the highest in Duroc pigs. In the present study, the mean value of IMF contents (%) of Longissimus dorsi muscle in Shanzhu × Duroc crossbreds was 2.53.…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al (2013) also presented the data that the IMF content was the highest in Duroc pigs. In the present study, the mean value of IMF contents (%) of Longissimus dorsi muscle in Shanzhu × Duroc crossbreds was 2.53.…”
Section: Discussionmentioning
confidence: 99%
“…It might be that the FTO protein differs with different phenotypes and splice variants, which could be more related to intramuscular fat content in different breeds (Tao et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A considerable number of studies concerning the porcine FTO gene have been reported (Du et al, 2009;Fan et al, 2009;Fontanesi et al, 2009Fontanesi et al, , 2010Zhang et al, 2009;Huang et al, 2010Huang et al, , 2011Tao et al, 2013). Numerous reports have provided evidence that the single nucleotide polymorphisms in the FTO gene are related to IMF deposition or IMF content in pigs (Fan et al, 2009;Fontanesi et al, 2009Fontanesi et al, , 2010Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%